Th(1)/Th(2) Cytokine Profile and Its Diagnostic Value in Mycoplasma pneumoniae Pneumonia - Li, Wei (Iran J Pediatr, 2016)
BACKGROUND: The levels of Th(1)/Th(2) cytokine can alter in pathogenic infection in children with pneumonia. OBJECTIVES: To evaluate Th(1)/Th(2) cytokine profile and its diagnostic value in M. pneumoniae pneumonia in children. PATIENTS AND METHODS: Children with M. pneumoniae mono-infection and 30 healthy children were tested with cytokines assay. We used real time PCR to detect M. pneumoniae in children with pneumonia. RESULTS: M. pneumoniae test was positive in 2188 (16.62%) out of 13161 pneumonia children. Children aged 5 - 9 years had the highest rate and summer was a season with high rate of M. pneumoniae incidence in Zhejiang province. During the course of study, in 526 pneumonia children with M. pneumoniae mono-infection and 30 healthy children cytokines assay was performed. IL-2 level of M. pneumoniae pneumonia children was lower than that of healthy children (median levels, pg/mL: IL-2: 3.2 vs. 5.7, P = 0.00), while IL-4, IL-10 and IFN-γ were higher than in healthy children (median levels, pg/mL: IL-4: 3.2 vs. 1.5, P = 0.00; IL-10: 5.6 vs. 2.5, P = 0.001; IFN-γ: 20.4 vs. 4.8, P = 0.001). CONCLUSIONS: IL-2 decreases and IL-4, IL-10 and IFN-γ increase in children with M. pneumoniae pneumonia, which has a promising prospect in diagnosis of this disease in clinical practice.